2019
DOI: 10.5603/fm.a2018.0095
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations and dimensions of arteries in the anterior part of the circle of Willis

Abstract: Background: The aim of this study was to investigate different anatomic variations and dimensions of anterior part of the circle of Willis (CW) and their prevalence on Kosovo's population. Materials and methods: This is an observational descriptive and retrospective study performed at the University Clinical Centre, Clinic of Radiology. The three-dimensional time-of-flight technique was used for magnetic resonance angiography imaging to evaluate the anatomy of the CW in 513 adults without clinical manifestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 11 publications
1
11
1
1
Order By: Relevance
“…The prevalence of complete anterior CW in this study was higher than an MRA-TOF study by Sherif Mohamed Zaki et al on 100 patents with no evidence of cerebrovascular disease which showed a prevalence of 66% [25]. The finding in our study was also higher than an MRA-TOF study by Shartri J et al on 513 adults without cerebrovascular disease which demonstrated a complete anterior CW in 64.3% [26]. The higher prevalence of a complete anterior CW in our study could be due to higher spatial resolution of CTA as compared to MRA, sample size differences, and racial differences.…”
Section: Discussioncontrasting
confidence: 70%
“…The prevalence of complete anterior CW in this study was higher than an MRA-TOF study by Sherif Mohamed Zaki et al on 100 patents with no evidence of cerebrovascular disease which showed a prevalence of 66% [25]. The finding in our study was also higher than an MRA-TOF study by Shartri J et al on 513 adults without cerebrovascular disease which demonstrated a complete anterior CW in 64.3% [26]. The higher prevalence of a complete anterior CW in our study could be due to higher spatial resolution of CTA as compared to MRA, sample size differences, and racial differences.…”
Section: Discussioncontrasting
confidence: 70%
“…The anterior circle variations are of great clinical importance as cerebral infarct due to occlusion of ACA is common [24]. We detected seven anterior circle variations out of the ten reported types.…”
Section: Resultsmentioning
confidence: 78%
“…The diameters of the arteries of the anterior and posterior circles were verified in Tables 4 and 5. Finally, the differences between the mean diameter of the was found to be the most sensitive method in the evaluation of COW arteries [24].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently studies have examining the vascular component of the head region of different animal species by using the corrosion cast technique (1,19). This technique is used to visualize hollow or virtual anatomical spaces.…”
Section: Introductionmentioning
confidence: 99%